Urgensi Prinsip Demokrasi dalam Etika Lingkungan untuk Menjamin Partisipasi Masyarakat dan Keadilan Antar Makhluk Hidup (International Forum of Researchers and Lecturers, 2025)
Many phenomena are present and occur in human life, both those with major impacts and those with relatively small impacts, and of course the impact of these will also be felt well. The environmental crisis remains a trending topic in the global scope due to the impact and impact of the deteriorating environmental conditions itself. The natural crisis has a very large impact, pressuring the life of humanity in the process of survival. Not only does it impact humans, but there is a large tendency to impact cosmological concepts. The threat to humanity from this phenomenon as an ecological crisis, demands a strong and good contribution in striving for nature in the context of preserving and restoring nature itself. It cannot be denied that the role of nature is truly enormous for human life, so it is very necessary to take action that can protect and care for nature, not the opposite to exploit nature itself. A local conceptual-based action that involves the community itself is a solution in monitoring and restoring the condition of nature to the present. Environmental ethics need to be built within the scope of society in a context that is directly in contact with nature, which is none other than the elements of nature itself. Communities must take swift action to address this visibly deteriorating natural environment. This study employed a qualitative research method with a literature review approach. The study found that the concept of community democracy, in its efforts to maintain justice among living things, has a positive impact as a collective contribution to protecting and restoring nature in its crisis context.